PJMHS 2023
DOI: 10.53350/pjmhs2023171455
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Open Versus Laparoscopic Surgery for Colorectal Cancer in the Emergency Setting

Abstract: Aim: The study aim is to do the comparison of oncological and short-term results of open and laparoscopic surgery for colorectal cancer in emergency setting. Study Design: This retrospective cohort research was held in the Department of Surgery, Civil Hospital, Karachi and Sheikh Zayed Medical College/ Hospital, Rahim Yar Khan for two-years duration from January 2020 to December 2021. Patients and Methods: after approval of this study and an informed consent agreement was signed by each participant. We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…Kumari et al [28] highlighted that open surgery had a higher incidence of T4 tumors, perforation, and obstruction compared with laparoscopic surgery in CRC cases. The study suggested that laparoscopic surgery in emergencies benefits CRC patients and should be considered by skilled surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Kumari et al [28] highlighted that open surgery had a higher incidence of T4 tumors, perforation, and obstruction compared with laparoscopic surgery in CRC cases. The study suggested that laparoscopic surgery in emergencies benefits CRC patients and should be considered by skilled surgeons.…”
Section: Discussionmentioning
confidence: 99%